Identification of Community-Based Agricultural Zakat Implementation: - Muttaqin, Aminnullah Achmad; Anggraini, Ika Khusnia; Ekawaty, Marlina; Azizi, Naurah Nadzifah (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Indonesia is an agricultural country where most of the population works as farmers, the agricultural sector is one of the main sectors of the country's economy. In line with that, statistical data proves that the agricultural sector is still the most important sector in supporting national economic development, especially during the recent pandemic that hit the world where the agricultural sector is at a stable pace compared to other sectors. Temboro Village has a unique culture in terms of the local community that distinguishes it from other villages, namely the concept of Madinah village with a distinctive culture based on certain Islamic ideologies. The research intends to identify the process of agricultural zakat implementation in the village of Temboro and is expected to contribute to the development of agricultural zakat implementation in other areas in Indonesia. The qualitative research method is used with an interpretive approach in a case study where the researcher is involved in sharing experiences with participants in Temboro Village. The results of the study prove that the management of agricultural zakat in Temboro Village is still categorized as traditional. There is no official (amil) zakat institution (LAZ) in Temboro Village. The system of collecting and distributing agricultural zakat is more emphasized on agricultural zakat and infaq which makes the mosque and boarding school the center. The problem in collecting agricultural zakat is not only that individual agricultural land ownership is relatively small but also not all farmers in Temboro village pay their agricultural zakat, so the percentage of agricultural zakat is not optimal and is distributed directly to the village community.